Reliability, Validity and Psychometric Properties of the Greek Translation of the Center for Epidemiological Studies-Depression (CES-D) Scale - Sitzoglou Konstantinos; Kaprinis Stergious G; Samolis Stavros; Kleanthous Soula; Iacovides Apostolos; Fountoulakis Konstantinos; St Kaprinis George; Bech Per (BMC Psychiatry, 2001)
Abstract Introduction The aim of the current study was to assess the reliability, validity and psychometric properties of the Greek translation of the Center for Epidemiological Studies- Depression Scale (CES-D). Methods 40 depressed patients 29.65 ± 9.38 years old, and 120 normal controls 27.23 ± 10.62 years old entered the study. In 20 of them (12 patients and 8 controls) the instrument was re-applied 1-2 days later. Translation and Back Translation was made. Clinical Diagnosis was reached by consensus of two examiners with the use of the SCAN v.2.0 and the IPDE. Statistical Analysis included ANOVA, the Pearson Product Moment Correlation Coefficient, Principal Components Analysis and Discriminant Function Analysis and the calculation of Cronbach's alpha (α) Results Both Sensitivity and specificity exceed 90.00 at 23/24, Chronbach's alpha for the total scale was equal to 0.95. Factor analysis revealed three factors (positive affect, irritability and interpersonal relationships, depressed affect and somatic complains). The test-retest reliability was satisfactory (Pearson's R between 0.45 and 0.95 for individual items and 0.71 for total score). Conclusion The Greek translation of the CES-D scale is both reliable and valid and is suitable for clinical and research use with satisfactory properties. Its properties are similar to those reported in the international literature. However one should always have in mind the limitations inherent in the use of self-report scales.